Design of a Disaster Recovery Plan Document at the Daniel S. Lev Law Library - Saputra, Dwi Fajar; Muzakir, Fahmi Arya; Zahra, Kaira Naafila; Amalia, Syifa Rizki; Fitriana, Shanata Zahwa; Firmansyah, Zhahiru Rafli; Murazaki Sani, Muhammad Mizan (Jurnal Tadwin, 2025)
A Disaster Recovery Plan (DRP) should be tailored to an institution's specific needs and characteristics in order to maintain information service continuity amid potential vulnerabilities in the information system. A qualitative approach was used to collect data through observations, semi-structured interviews with the library director and IT staff, and internal documentation studies. The Daniel S. Lev Law Library uses various systems for daily operations and is highly dependent on five main information systems: Digilev, the Institutional Repository, Catalog Danlev, the Court Decisions System, and the Internal Archiving System. The analysis of critical information systems and potential risks was based on the NIST SP 800-34 Rev. 1 framework and the FIPS 199 guidelines. The results showed that Digilev and the Institutional Repository had the highest impact levels because they are directly related to academic research and accreditation requirements. Additionally, we conducted Recovery Time Objective (RTO) and Recovery Point Objective (RPO) identification to establish priorities for effective information system recovery strategies based on disruption scenarios such as server downtime, cyber threats, and natural disasters. These strategies include providing backups and backup servers, enhancing system security, training staff, and creating emergency plans for physical disasters. These results are all documented in a structured disaster recovery plan that serves as a technical guide and institutional regulation for anticipating and addressing issues that could disrupt the information system. It is hoped that this plan will enhance security and ensure the continuity of digital library services at the Daniel S. Lev Law Library.